2020
DOI: 10.3389/fmicb.2020.02104
|View full text |Cite
|
Sign up to set email alerts
|

Functional Profile of Human Cytomegalovirus Genes and Their Associated Diseases: A Review

Abstract: The human cytomegalovirus (HCMV), whose genome is 235 ± 1.9 kbp long, is a common herpesvirus. However, the functions of many of its genes are still unknown. HCMV is closely associated with various human diseases and infects 60-90% of the global population. It can infect various human cells, including fibroblasts, epithelial cells, endothelial cells, smooth muscle cells, and monocytes. Although HCMV infection is generally asymptomatic and causes subtle clinical symptoms, it can generate a robust immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 159 publications
(228 reference statements)
0
28
0
Order By: Relevance
“…T cell responses to hCMV immediate-early antigen 1 (IE1) regardless of the HIV status and ages. As its name states, IE1 is amongst the earlies transcripts of hCMV and is transcribed early both in the course of primary infection and reactivation (Ye et al 2020), explaining ubiquitous and strong T cell stimulation by this antigen. T cell responses against pp65, a late-transcribing major tegument phosphoprotein (Ye et al 2020), were more pronounced in the HIV+ younger group, consistent with the idea that the higher cytokine response in HIV+ participants likely reflects strong hCMV reactivation/ precipitated by the HIV infection itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T cell responses to hCMV immediate-early antigen 1 (IE1) regardless of the HIV status and ages. As its name states, IE1 is amongst the earlies transcripts of hCMV and is transcribed early both in the course of primary infection and reactivation (Ye et al 2020), explaining ubiquitous and strong T cell stimulation by this antigen. T cell responses against pp65, a late-transcribing major tegument phosphoprotein (Ye et al 2020), were more pronounced in the HIV+ younger group, consistent with the idea that the higher cytokine response in HIV+ participants likely reflects strong hCMV reactivation/ precipitated by the HIV infection itself.…”
Section: Discussionmentioning
confidence: 99%
“…As its name states, IE1 is amongst the earlies transcripts of hCMV and is transcribed early both in the course of primary infection and reactivation (Ye et al 2020), explaining ubiquitous and strong T cell stimulation by this antigen. T cell responses against pp65, a late-transcribing major tegument phosphoprotein (Ye et al 2020), were more pronounced in the HIV+ younger group, consistent with the idea that the higher cytokine response in HIV+ participants likely reflects strong hCMV reactivation/ precipitated by the HIV infection itself. The finding that older HC older subjects "catch up" with HIV+ participants in their T cell anti-pp65 responses is likely reflective of the repeated rounds of hCMV subclinical reactivation over time in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Since the two oncogenic herpesviruses discovered so far, Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) exploit both latency and low lytic viral replication to fuel the oncogenic process (9)(10)(11), we decided to study HCMV genes and proteins expressed in CTH cells, even at low levels. In this context, studies have shown that few HCMV genes such as UL123 and UL122 immediate early genes, UL7, UL111A, UL112, US28, US33, UL135, UL136, and lncRNA4.9 could be responsible for the tumorigenic phenotype observed in some human malignancies (12). Previously, we detected the presence of a 126 bp amplicon corresponding to the sequence of lncRNA4.9 gene (nt95592-nt95717) of HCMV-DB strain in CTH cells (6).…”
Section: Introductionmentioning
confidence: 85%
“…HCMV, thanks to its continuous co-evolution with the host, has developed an arsenal of immune escape mechanisms to counteract the immune system, particularly the “unwanted” inflammation [ 38 , 39 , 40 , 41 ]. These “viral gambits” are discussed below.…”
Section: Modulation Of the Immune System By Hcmvmentioning
confidence: 99%
“…The initial intracellular response is triggered by pattern recognition receptors (PRRs), which after detecting pathogen-associated molecular patterns (PAMPs) can activate a downstream signaling pathway leading to the production of type I IFN and the release of pro-inflammatory cytokines. Also in this case, HCMV has devised different strategies to circumvent innate immunity [ 40 , 48 , 49 ]. For instance, our group has recently shown that the HCMV tegument protein pp65—also known as pUL83—binds to cyclic guanosine monophosphate–adenosine monophosphate synthase (cGAS), thereby inhibiting its ability to stimulate IFN-β production [ 50 ].…”
Section: Modulation Of the Immune System By Hcmvmentioning
confidence: 99%